2010
DOI: 10.1248/bpb.33.816
|View full text |Cite
|
Sign up to set email alerts
|

Shikonin Induces Apoptosis through Reactive Oxygen Species/Extracellular Signal-Regulated Kinase Pathway in Osteosarcoma Cells

Abstract: Shikonin, a major ingredient in the Chinese traditional herb Lithospermum erythrorhixon, exhibits multiple biological functions including antimicrobial, anti-inflammatory, and antitumor effects. In this study, we delineated the molecular mechanisms of shikonin in the apoptosis of 143B osteosarcoma cells. Shikonin reduced the cell viability of 143B cells in a dose-and time-dependent manner. The IC 50 at 24 h and 48 h for 143B cells was 4.55 and 2.01 m mM, respectively. A significantly elicited hypodiploid cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
65
1
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 89 publications
(74 citation statements)
references
References 34 publications
3
65
1
4
Order By: Relevance
“…Shikonin is also reported to influence apoptosis to some extent (Chang et al 2010;Liu et al 2014) and can regulate the AKT/ASK1/p38 pathway or reactive oxygen species levels to induce apoptosis (Ahn et al 2013;Duan et al 2014;Lee et al 2014). Our study revealed that a low concentration of shikonin has no apparent effect on apoptosis, but in the presence of TNF-␣, shikonin induces apoptosis in a concentrationdependent manner, promotes the activation of caspase-3 and (G, H) The expression levels of cyclin D1 and cyclin E were measured by Western blot after treatment with different concentrations of shikonin and TNF-␣.…”
Section: Discussionmentioning
confidence: 99%
“…Shikonin is also reported to influence apoptosis to some extent (Chang et al 2010;Liu et al 2014) and can regulate the AKT/ASK1/p38 pathway or reactive oxygen species levels to induce apoptosis (Ahn et al 2013;Duan et al 2014;Lee et al 2014). Our study revealed that a low concentration of shikonin has no apparent effect on apoptosis, but in the presence of TNF-␣, shikonin induces apoptosis in a concentrationdependent manner, promotes the activation of caspase-3 and (G, H) The expression levels of cyclin D1 and cyclin E were measured by Western blot after treatment with different concentrations of shikonin and TNF-␣.…”
Section: Discussionmentioning
confidence: 99%
“…In general, ERK-mediated growth factors enhance cell proliferation, whereas JNK and p38 kinases transduce signals from stress and inflammation to promote apoptosis (26). Flavonoid-triggered cancer cells undergo apoptosis through the modulation of MAPK protein kinases (27)(28)(29). Epigallocatechin-3-gallate (EGCG) inhibits ERK activation and increases p38 kinases and JNK activity, which subsequently enhances apoptosis in pancreatic cancer cells (30).…”
Section: Discussionmentioning
confidence: 99%
“…The anticancer effects of SHK have been investigated in numerous prior studies (18)(19)(20)(21)(22)(23)(24). SHK is not toxic to normal cells (25), but exerts cytotoxic effects against various neoplastic cells, and has not been demonstrated to promote anticancer drug resistance (26).…”
Section: Introductionmentioning
confidence: 99%